Health Effects of Ambient Air Pollution How safe is the air we breathe? - Koenig, Jane Q. (Springer US, 2000)
Health Effects of Ambient Air Pollution provides the reader with an overview of the health effects of air pollution in human subjects. The majority of the book is devoted to the discussion of the health effects of common widespread air pollutants regulated by the U.S. Environmental Protection Agency through national ambient air quality standards. The book reviews the sources and fate of common air pollutants in ambient air and researches the adverse effects of these outdoor and indoor air pollutants in 'in vivo' cell systems, animals, and humans. Research for the book was conducted in controlled laboratory studies and epidemiologic studies. Special emphasis throughout Health Effects of Ambient Air Pollution is placed on the effects of air pollution in subjects with asthma